Loan Management of Nabil Bank and Everest Bank: A Comparative Study - Shrestha, Sanjay (Academic Voices: A Multidisciplinary Journal, 2018)
The study focuses on loan management of two commercial banks with reference of Nabil and Everest Bank of Nepal and its impact on profitability. This paper reports the comparative study of deposit, loan, ROA, ROE and CV. Descriptive research approach is applied for the readily available five years performance data from 2011/12 to 2015/ 16. Both of the banks have u lized most of the funds in the form of credit and advances which is the major part of ut ilizing deposits for income generat ing purpose. On the average, both Nabil and Everest bank have utilized its total deposits constant in consecutive years. Likewise, the mean ratio of total loan to total deposit of Nabil and Everest bank are 70.75% and 72.54% respectively. By coefficient variation analysis, Everest has more uniformity than Nabil since Everest has less CV of 6.16%. It can be concluded that the higher mean rat io indicates the good lending performance. Academic Voices Vol.6 2016: 47-54